Frequency Of Prolonged Qtc in Patients With Decompensated Chronic Liver Disease In A Rural Cohort Of Sindh - Ahmed, Adeel; Rabbani, Bushra; Kamran, Muhammad; Saeed, Ammarah; Ahmed, Jameel (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the frequency of prolonged QTc (corrected QT) interval in patients. With decompensated chronic liver disease (DCLD) in a tertiary care hospital of Gadap town, Sindh. Methods: This cross-sectional study was conducted from 1st January 2022 to 31 December 2022 at the Department Of Medicine, Baqai Medical University, Karachi. All partial and fully decompensated Cirrhotic patients aged 25 to 75 years regardless of sex, diagnosed based on history, physical Examination and ultrasonography findings, who were admitted to our medical ward, were included using a non-probability convenience sampling technique. Pregnant females, patients with other major co-morbid illnesses, electrolyte imbalances and those on medications affecting QTc interval were excluded. All patients meeting inclusion criteria were enrolled for a 12 lead ECG (three serial recordings each), from which QT, R-R interval, as well as QTc, were calculated. Data entry and analysis were performed using SPSS version 20. Categorical variables were described using frequency and percentages whereas continuous variables were summarized using mean and standard deviation. Results: Out of 196 participants with decompensated liver disease included in the study, 59 (30.1%) participants were found to have prolonged QTc. Age, Child–Turcotte–Pugh (CTP) class and Bilirubin of the patients were significantly associated with QTc prolongation. Conclusion: Prolonged QTc interval, a marker of cirrhotic cardiomyopathy, is a common occurrence in patients with decompensated chronic liver disease. The risk of developing prolonged QTc interval increases with advanced age and progressive liver disease.